Storage and disposal practices of unused and expired medications among adult women attending Banadir Hospital, Mogadishu, Somalia: A cross-sectional study - Abdiweli Mohamed Abdi; Osman Mohamed Mohamud; Mohamed Ismail Iman; Nor Haji Osman; Ahmed Abdulkadir Kalif; Mahad Ali Mohamud; Abdinor Hussein Ahmed; Mohamed Yusuf Isak (PLoS ONE, 2026)
Improper storage and disposal of unused and expired medications in households pose significant environmental and public health risks. A cross-sectional study was conducted in November 2025 among 427 consecutively selected women visiting the outpatient pharmacy of Banadir Hospital to assess storage and disposal practices of unused and expired medications. Data were analyzed using descriptive statistics, while associations between socio-demographic characteristics and medication storage and disposal practices were assessed using the chi-square test and interpreted with Cramér’s V. Most respondents reported storing unused medications at home (97%), mainly for emergency situations, while more than one-third also kept expired medications at home (34%). Nearly all participants did not read storage instructions on medication labels (98%), and most did not check expiration dates before purchasing (70%) or using medications (74%). Disposal practices were inappropriate in most cases, with over 90% reporting disposal in household trash. These findings indicate that improper medication storage and disposal practices are highly prevalent in this setting. Public awareness programs and the establishment of a national drug take-back system are needed to reduce environmental contamination, prevent medication misuse, and improve public health safety.